PENGARUH REWARD TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA DALAM ILMU NAHWU SISWA KELAS VIII SMP TAHFIDZ AL-ITTIBA’ KLATEN - Mohammad Alfin Ni'am; Abdul Basid (STAI Ali bin Abi Thalib Surabaya, 2022)
Arabic lessons, especially Nahwu, are known among students as difficult, boring, and uninteresting lessons. One of the reasons is because of the lack of variations in the methods applied in their learning. Another obstacle is the students' laziness and no motivation to succeed in mastering Arabic. The purpose of this study was to examine the effect of rewards on motivation and learning outcomes of Nahwu science students in class VIII SMP Tahfidz Al-Ittiba' Klaten. Reward is everything that is given by the teacher in the form of respect that pleases students on the basis of the good results that have been achieved in the educational process, the goal is to motivate students to do things that are commendable and try to improve achievement. This research was conducted at SMP Tahfidz Al-Ittiba' Klaten for 5 face-to-face meetings with a population of 5 students. This research is a Tajribi (experimental) research with a pre-experimental approach and a mixed type of research. The research instrument consisted of observations, interviews, questionnaires, and tests in the form of pre-test and post-test. The results showed that the method of giving rewards had a significant effect on increasing students' learning motivation both inside and outside the classroom. The reward method also has a significant effect on improving student learning outcomes in Arabic subjects in the Nahwu science category.